Where does plastic waste go? Local dynamics of waste flows in Indonesian neighbourhoods - Giulia Frigo; Christian Zurbrügg; Iwan Juwana; Claudia R. Binder (Environmental Challenges)
This study examines plastic waste flows across administrative wards (Kelurahan) and neighbourhoods (Rukun Warga) in Bandung, Indonesia, focusing on the role of local source separation programs, socioeconomic factors, and infrastructures in shaping plastic waste consumption and disposal practices. Using a bottom-up, geo-referenced approach to Material Flow Analysis (MFA), the study found that household plastic waste consumption ranges from 14 to 20 kg per capita per year. On average, more than 50% of plastic waste is sent to landfill, about 25–30% is source-separated, around 12% remains uncollected, and a small portion (1–2%) is burned.The analysis reveals significant disparities in plastic waste consumption and disposal practices among kelurahan, with notable variations across all examined waste flows. Wards and neighbourhoods exhibit distinct dynamics, local governance structures and resources, and are home to people with different socioeconomic backgrounds. Our findings show that plastic consumption is higher in wealthier households, while source-separated plastic waste is higher among households with both higher education and income levels. Source-separation initiatives at the neighbourhood level emerged as the most significant factor influencing source separation, with one kelurahan demonstrating a markedly higher source-separated waste rate. However, limited infrastructure and collection capacity lead to higher burning and uncollected waste which primarily accumulates along river flows and open spaces near houses. The results highlight the need for localised approaches to waste management that address the specific needs and challenges of individual wards and neighbourhoods. Strengthening local governance, expanding waste collection infrastructure, fostering stakeholders’ collaboration and community-based programs can enhance the efficiency of plastic waste management. Such insights are essential for developing effective waste management strategies tailored to specific local needs, offering valuable guidance for policymakers addressing the challenges of plastic waste in rapidly urbanising areas like Bandung.